The Role of Investment Opportunity Set (IOS), Firm Age, and Managerial Ownership in Increasing Company Value - Rismawandi; Martini (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The value of a company is one of the main considerations for investors when deciding to invest. A high company value reflects positive investor perceptions and indicates that the company has good future prospects. This research aims to analyze the effect of the investment opportunity set, company age, and managerial ownership on firm value. The study was conducted on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. The sampling technique used in this study is purposive sampling, where the sample is selected based on specific criteria relevant to the research objectives. As a result, 10 companies that met the criteria were chosen as the sample. The analytical method employed is multiple linear regression analysis, processed using the SPSS Version 26 software. The results of the study indicate that the investment opportunity set and company age do not have a statistically significant influence on firm value. In contrast, managerial ownership has a positive and significant effect on firm value. These findings suggest that the greater the ownership of shares by management, the more aligned management’s interests are with those of shareholders, thereby increasing firm value. The company value can be explained by its independent variables, namely the investment opportunity set, company age, and managerial ownership by 11.3%.